RELAÇÃO ENTRE PRECIPITAÇÃO PLUVIOMÉTRICA E PRODUTIVIDADE DA CULTURA DE SOJA, NO MUNICÍPIO DE IBIRUBÁ-RS - Silva, Robson Rigão da; Sartori, Maria da Graça Barros; Wollmann, Cássio Arthur (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2014)
The present research concerns in evaluate the relationship between pluviometric precipitation and soybean productivity in the municipality of Ibirubá-RS, as a case study, in a period of 31 years (1982-2012). The results have been organized according to the methodological proposal of this work, in other words, based on precipitation criterion, which was subdivided into: precipitation below the usual, precipitation usual and precipitation above the usual. This way, the total of pluviometric precipitation influence the yields of soybeans, but it was verified that the hydric distribuition during the phenological cycle, in highlighted the moments with higher hydric requirement, vegetative phase of emergency and reproductive of grain filling have become essential for the final yields. Even with the introduction of new technologies in cultivars, such as soybeans indeterminate growth, variability of pluviometric precipitation is still influential in productivity.